Assistance for the Sitiwinangun Pottery Village Tourism through Digital Marketing Activities with Local Wisdom - Wardiyanto, Yayan; Dewi, Wulan Kartika; Trisolvena, Muhammad Nana; Maulana, Sofik (Society : Jurnal Pengabdian Masyarakat, 2025)
Sitiwinangun Village has high potential as a center for pottery tourism villages in Cirebon Regency. However, there are obstacles to the success of digital promotion, namely the ineffectiveness of the promotion. This community service activity aimed to create digital promotional media (brochures, catalogs, e-catalogs, and video content) that will be uploaded on Tiktok social media. The partners of this activity were the staff and pottery craftsmen of the Sitiwinangun tourist village. This activity consisted of the stages of observation, problem identification, implementation of marketing activities, and evaluation. This activity has been successfully implemented, and brochures, catalogs, e-catalogs, and promotional video content for the Sitiwinangun Pottery Village tourist village have been produced. The media that has been created has also been actively promoted on Tiktok social media. Evaluation of the total number of video content viewers on social media for 3 weeks with the results of 4000-5000 viewers. The results of this activity are expected to contribute positively, especially in terms of increasing the number of visitors to tourist attractions and the number of pottery buyers in Sitiwinangun Village.